Government Policy and Performance of Agricultural Cooperatives: A Case Study in Chitwan District, Nepal - Dinesh Dhakal (MDPI AG, 2021)
Agricultural cooperatives are producer-owned and controlled organizations to improve farmers’ livelihoods by correcting market failure. They support collective activities where individual incentives are insufficient to produce public goods. The government of Nepal has been investing economic resources in this sector, prioritizing cooperatives as part of a strategy for poverty reduction. This study examines poor farmers’ access to agricultural cooperatives and the impact of membership on farm and total household income, based on a household survey of 572 households and key informant interviews of 37 cooperative managers. The ethnicity of the family and the neighborhood, smallholder land size, distance to an agricultural cooperative, distance to the nearest local market, and distance to a motorable road are key determinants that influence cooperative membership. The analysis of the effects of cooperative membership is based on propensity score matching, controlling for a large array of household and community characteristics. The estimates imply that cooperative membership may significantly affect family net crop income, but the overall effects on total family income are modest. Agricultural cooperatives appear to be focused on financial services such as savings and credit activities but are less concerned with agricultural production, and cooperatives engage in almost no marketing activities.